2022
DOI: 10.1177/21925682221116819
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preoperative Marijuana Use on Surgical Outcomes, Patient-Reported Outcomes, and Opioid Consumption Following Lumbar Fusion

Abstract: Study Design Retrospective Cohort Study. Objectives To (1) investigate the effect of marijuana use on surgical outcomes following lumbar fusion, (2) determine how marijuana use affects patient-reported outcomes measures (PROMs), and (3) determine if marijuana use impacts the quantity of opioids prescribed. Methods Patients > 18 years of age who underwent primary one- or two-level lumbar fusion with preoperative marijuana use at our institution were identified. A 3:1 propensity match incorporating patient de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
0
14
1
Order By: Relevance
“…A review of 240 patients by Lambrechts et al25 studied outcomes of patients who underwent primary 1- to 4-level anterior cervical discectomy and fusion surgeries, 60 of whom used marijuana preoperatively. Another retrospective review by D'Antonio et al26 looked at 259 patients who underwent lumbar spine fusion, 65 of whom used marijuana preoperatively. Both of these studies showed that marijuana did not affect postoperative opioid consumption 25,26.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A review of 240 patients by Lambrechts et al25 studied outcomes of patients who underwent primary 1- to 4-level anterior cervical discectomy and fusion surgeries, 60 of whom used marijuana preoperatively. Another retrospective review by D'Antonio et al26 looked at 259 patients who underwent lumbar spine fusion, 65 of whom used marijuana preoperatively. Both of these studies showed that marijuana did not affect postoperative opioid consumption 25,26.…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective review by D'Antonio et al26 looked at 259 patients who underwent lumbar spine fusion, 65 of whom used marijuana preoperatively. Both of these studies showed that marijuana did not affect postoperative opioid consumption 25,26. One major limitation of these retrospective studies is that participants were classified as marijuana users or nonusers but were not further stratified by pre- or postoperative use, frequency and quantity of use, duration of use, or route of administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of 240 patients by Lambrechts et al 25 studied outcomes of patients who underwent primary 1-to 4-level anterior cervical discectomy and fusion surgeries, 60 of whom used marijuana preoperatively. Another retrospective review by D'Antonio et al 26 looked at 259 patients who underwent lumbar spine fusion, 65 of whom used marijuana preoperatively. Both of these studies showed that marijuana did not affect postoperative opioid consumption.…”
Section: Postoperative Opioid Use and The Potential For Marijuanamentioning
confidence: 99%
“…In addition, the review by D'Antonio et al found that marijuana users were more likely to have a spine reoperation within 3 years (P = 0.041) but did not find any significant differences in surgical outcomes or patient-reported outcomes between the 2 groups. 26 All these studies have similar limitations in that they do not define the quantity, timing, or route of administration of marijuana use.…”
Section: The Impact Of Marijuana On Surgical Outcomesmentioning
confidence: 99%